Learning cooperation from the commons - Erling Berge (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2019)
The paper discusses the link between commons as they might have been used in prehistoric Norway and the rules concerning the exploitation of the commons as found in the oldest known legislation for regions of Norway, Gulating Law and Frostating Law. One clear social dilemma has been identified: the setting of a common date for moving animals from the home fields up to the summer farms and home again in the fall. The problem was obvious and the solution not particularly difficult to institute. Many more problems were of course present, but they did not rise to the level of a social dilemma. All such problems were managed by the rules enacted by the bygdeting along with other problems of a community. In particular the process of inheritance, the problems of fencing, how to change borders between neighbours and between individually owned fields and the commons, were treated by extensive rules. The bygdeting managed such issues from prehistory until the 16th and 17th centuries when reforms initiated by the Danish-Norwegian kings started to take effect, making the rule-of-law more uniquely a task for the central authorities and of less concern for the local communities. Maybe the basic legacy of the long history of local rule was a strong belief in the court system, that it would secure the old saying: "By law the land shall be built, not with unlaw wasted".
Keywords: K11; P48; Q15; Q20; Z13; 330; Commons; prehistory; Norway; social dilemmas; legislation